(untitled) (Minerva, 2019)
1. Acc., Ab. and D. depend on the meaning of per modum fluxus: Acc. and Ab. (on their own or following a preposition) involve the physical features of movement; the Dative involves the non-physical or teleological features (subsequently they carry no preposition). 2. The Dative case always appears with its significatum or value: the direction in the instances of the socalled «directional dative» can only be found in the context and in the designatum. 3. The Dative case also has its value when in dependance of prefixed verbs: the physical features of movement are expressed by the verbal prefix; the non-physical features are expressed by the Dative. 4. The fact that there is no coincidence between Latin and Spanish with respect to inner-form, system and usage makes it extremely difficult to translate the significatum of the Dative case.